Discovery of 2-[2-(5-nitrofuran-2-yl)vinyl]quinoline derivatives as a novel type of antimetastatic agents. Issue 1 (1st January 2015) - Tseng, Chih-Hua; Tzeng, Cherng-Chyi; Chiu, Chien-Chih; Hsu, Chih-Yao; Chou, Chon-Kit; Chen, Yeh-Long
Graphical abstract